Collaborative intelligence : thinking with people who think differently - Markova, Dawna, 1942- (Spiegel & Grau, 2015)
"We are living in a hinge time when the way that we think, interact, and innovate at work is rapidly changing. In the past, "Marketshare" companies dominated, ruled by hierarchy and top-down leadership. Today, the new market leaders are "Mindshare" companies, where influence is more important than power and success relies on collaboration and the ability to inspire. Markova and McArthur believe that the key to collaborating effectively with our colleagues is respecting "intellectual diversity," the ways we think and process information differently. Each of us brings unique and varied thinking talents to the table, and when we understand intellectual diversity, we can come together like a symphony orchestra. Through fascinating exercises and revealing case studies, readers discover their own unique "Mind Patterns" and "Thinking Talents," and learn how to recognize the same in their colleagues. Collaborative Intelligence is the culmination of over 35 years of original research and draws upon Markova's background in neuroscience and her work as a "thinking partner" to Fortune 500 CEOs and some of the world's top creative talents. It is essential reading for anyone who works as part of a team, who manages others, or simply wants to better understand how people think"--